Quorum-sensing acts at initiation of chromosomal replication in Escherichia coli - Withers, Helen L. (The National Academy of Sciences, 1998)
Chromosomal replication in Escherichia coli was studied by flow cytometry and was found to be inhibited by an extracellular factor present in conditioned media collected during late exponential and early stationary phase, i.e., via a quorum-sensing mechanism. Our results suggest that the inhibitory activity of the extracellular factor is exerted during initiation of DNA replication rather than during elongation. Furthermore, we present evidence that this interaction may occur directly at each of the replication forks. Unlike other quorum-sensing systems described so far for Gram-negative bacteria, this inhibitory activity does not require transcription or translation to be effective. Implications of quorum-sensing regulation of DNA replication are discussed.